Using Human Milk Fortifiers to Improve the Preoperative Nutritional Status of Infants With Non-restricted Ventricular Septal Defect - Lin, Yun-Feng; Lin, Wen-Hao; Lin, Shi-Hao; Zhang, Qi-Liang; Chen, Qiang; Zheng, Yi-Rong (Frontiers in Pediatrics, 2022)
Objective: To explore the effects of human milk fortifier (HMF) on improving the preoperative nutritional status of infants with nonrestricted ventricular septal defect (VSD). Methods: A prospective randomized controlled study was conducted in a provincial hospital in China. Participants were randomly divided into an intervention group (n = 29) and a control group (n = 29). HMFs were added proportionally to the infants’ feeds in the intervention group based on breastfeeding status, and the infants in the control group received exclusive breastfeeding as needed. The nutritional status of the two groups was compared one month after the intervention. Results: Compared with the control group, the weight, head circumference, height, albumin level, and prealbumin level of the human milk fortifier group were significantly higher one month after the intervention (p<0.05). The STRONGkids score of the HMF group was significantly lower than that of the non-HMF group (p<0.05). There was no significant difference in pneumonia, liver insufficiency, feeding intolerance, or jaundice between the two groups. Conclusion: The addition of HMFs based on the breastfeeding status of infants with nonrestricted VSD can improve the preoperative nutritional status and does not increase the incidence of gastrointestinal complications.